Intravenous iron therapy improves the hypercapnic ventilatory response and sleep disordered breathing in chronic heart failure. (8th August 2022) - Caravita, Sergio; Faini, Andrea; Vignati, Carlo; Pelucchi, Sara; Salvioni, Elisabetta; Cattadori, Gaia; Baratto, Claudia; Torlasco, Camilla; Contini, Mauro; Villani, Alessandra; Malfatto, Gabriella; Perger, Elisa; et al.
Abstract : Aims: Intravenous iron therapy can improve symptoms in patients with heart failure, anaemia and iron deficiency. The mechanisms underlying such an improvement might involve chemoreflex sensing and nocturnal breathing patterns. Methods and results: Patients with heart failure, reduced left ventricular ejection fraction, anaemia (haemoglobin <13 g/dl in men; <12 g/dl in women) and iron deficiency (ferritin <100 or 100–299 μg/L with transferrin saturation <20%) were 2:1 randomized to patient‐tailored intravenous ferric carboxymaltose dose or placebo. Chemoreflex sensitivity cardiorespiratory sleep study, symptom assessment and cardiopulmonary exercise test were performed before and 2 weeks after the last treatment dose. Fifty‐eight patients (38 active arm/20 placebo arm) completed the study. Intravenous iron was associated with less severe symptoms, higher haemoglobin (12.5 ± 1.4 vs. 11.7 ± 1.0 mg/dl, p  < 0.05) and improved haematinic parameters. Ferric carboxymaltose improved the central hypercapnic ventilatory response (−25.8%, p  < 0.05 vs. placebo), without changes in peripheral chemosensitivity. In particular, the central hypercapnic ventilatory responses passed from 4.6 ± 6.5 to 2.9 ± 2.9 L/min/mmHg after ferric carboxymaltose and from 4.4 ± 4.6 to 4.6 ± 3.9 L/min/mmHg after placebo ( p treatment*condition  = 0.046). In patients presenting with sleep‐related breathing disorder, apnoea–hypopnoea index was reduced with active treatment as compared to placebo (12 ± 11 vs. 19 ± 13 events/h, p  < 0.05). After ferric carboxymaltose, but not after placebo, both peak oxygen uptake (VO2 ) increased (Δ1.1 ± 2.0 ml/kg/min, p  < 0.05) and VO2 /workload slope was steeper (Δ0.67 ± 1.7 L/min/W, p  < 0.01). Conclusions: Intravenous ferric carboxymaltose improves the hypercapnic ventilatory response and sleep‐related breathing disorders in patients with heart failure, anaemia and iron deficiency. These newly described findings, along with improved oxygen delivery to exercising muscles, likely contribute to the favourable effects of ferric carboxymaltose in anaemic patients with heart failure.